Pelatihan penyusunan rencana kegiatan dalam kebijakan dana desa - Muhammad Nuryamin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The most effective and faster direction forempowering rural communities to achieve goals through thepreparation of activities. The purpose of this communityservice is to increas the knowledge and skills of the villagecommunity in preparing activity plans, in relation to thevillage fund program in Arasoe Village of Bone Regency.Activities in this workshop covers lectures, question andanswer session, training and practice, discussion, andmentoring. This workshop involving members of communitygroups, youth organizations and village officials. The resultsshowed that the attendance during the workshop reached 85%,participants understand of the importance of empowering ruralcommunities through making plans for each activity and ableto make an action plan that could be realized. Most of themstill think that physical development is more important thanempowerment. Therefore, physical development is choose informulating activity plans. Community interest in makingplans for activities to develop the village means a lot to theimplementation of the village fund program.